Fire retardant materials - Horrocks, A. Richard; Price, Dennis, Professor (CRC Press ; Woodhead, 2001)
This is a comprehensive source of information on all aspects of fire retardancy. Particluar emphasis is placed on the burning behaviour and flame retarding properties of polymeric materials and textiles. It covers combustion, flame retardants, smoke and toxic products generally and then goes on to concentrate on some more material-specific aspects of combustion in relation to textiles, composites and bulk polymers. Developments in all areas of fire retardant materials are covered including research in new areas such as nanocomposition. Fire retardant materials is an essential reference source for all those working with, researching into, or designing new fire retardant materials. Detailed analysis of the burning behaviour and flame retarding properties of ploymers, composites and textilesCovers smoke and toxic gas generationAnalysis of material performance in fire.
Keywords: Fire resistant materials.; elektronické knihy; electronic books